Effective removal of organic pollutants using GeO2/TiO2 nanoparticle composites under direct sunlight. (5th February 2018) - Natarajan, Kalithasan; Bajaj, Hari C.; Tayade, Rajesh J.
Abstract : TiO2 and GeO2 /TiO2 nanoparticle composites were synthesized by solution combustion method are used as photocatalyst for removal of organic pollutants. Abstract : TiO2 and GeO2 /TiO2 nanoparticle composites were synthesized from titanium tetraisopropoxide, germanium oxide, dry ethanol, and diethanolamine using a solution combustion method. The synthesized catalysts were characterized using powder X-ray diffraction, UV-Vis diffuse reflectance spectroscopy, Brunauer–Emmett–Teller surface area analysis, Fourier transform infrared spectroscopy, Fourier transform Raman spectroscopy, scanning electron microscopy, and transmission electron microscopy. The photocatalytic degradation of rhodamine B (RhB) dye in aqueous solution (2.06 × 10 −5 M) was achieved using synthesized pristine TiO2 (P-T) and GeO2 /TiO2 (GT) nanoparticle composite catalysts under direct sunlight. Among the synthesized catalysts, 1-GT afforded 100% RhB degradation in aqueous solution within 180 min. Furthermore, 85, 87, and 83% degradation was achieved using P-T, 2-GT, and 3-GT nanoparticles, respectively. RhB degradation was confirmed by chemical oxygen demand and total organic carbon analyses.